2018
DOI: 10.1016/j.bioorg.2017.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Cunninghamella blakesleeana-mediated biotransformation of a contraceptive drug, desogestrel, and anti-MDR-Staphylococcus aureus activity of its metabolites

Abstract: Staphylococcus aureus is one of the most infectious agents among staphylococcal bacteria. Currently many strains of S. aureus have developed resistance against available antibiotics. Therefore, the treatment of infections caused by them is a major challenge. During current study, desogestrel (1), a contraceptive drug, was found to be a potent growth inhibitor of drug resistant strains of S. aureus. Therefore, in search of new and effective agents against multi-drug resistant S. aureus strains, whole-cell bio-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…An OH group at C-5 (d 77.0) was placed as a, based on the comparison of the reported chemical shis for 5a-OH in steroids. 15,20 Thus the structure of a new metabolite was identied as 2a-methyl-3b,5a,17b-trihydroxyandrostane (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An OH group at C-5 (d 77.0) was placed as a, based on the comparison of the reported chemical shis for 5a-OH in steroids. 15,20 Thus the structure of a new metabolite was identied as 2a-methyl-3b,5a,17b-trihydroxyandrostane (7).…”
Section: Resultsmentioning
confidence: 99%
“…12 Similarly, several metabolites of drostanolone on incubation with cryopreserved human hepatocytes are also reported. 13 In continuation of our structural transformation studies on steroidal drugs, [14][15][16][17][18][19][20] biotransformation of drostanolone heptanoate (1) was carried out. Based on small scale screening results, compound 1 was subjected to biotransformation by using two microbial cell cultures, Beauveria bassiana, and Macrophomina phaseolina, for the rst time, yielding seven new, and two known compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium oxysporum biotransformed to 126 in a mixture of four hydroxylated derivatives (127-129 and 130), which were characterized as their acetylated derivatives; the hydroxylation was favorably in C-7 stereospecifically (α orientation) in the 3β-hydroxy-Δ 5 -steroids, while Colletotrichum musae biotransformed to 126-127 by reducing the carbonyl group in C-17 ( Figure 16) [56]. In the biotransformation of 126 using Penicillium griseopurpureum and P. glabrum, the following was produced; hydroxylated derivatives in C-7α (95), C-14α (94) and C-15α (117), with 11 being the main product. In addition, P. griseopurpureum generated products for the Baeyer Villiger oxidation to give the lactone D ring (testolactone, 13) and its hydroxylated derivative at C-15α (15α-hydroxy-17α-oxa-d-homo-androst-4-en-3,17-dione, 135); while P. glabrum generated the compounds, 3β-hydroxy-17α-oxa-D-homo-androst-5-en-17-one (136) and 3β-hydroxy-17α-oxa-D-homo-5α-androstan-17-one (137) (Figure 16) [82].…”
Section: Microbiological Transformations Of Steroidsmentioning
confidence: 99%
“…The ethynodiol diacetate (192) is a synthetic derivative 1, used as an oral contraceptive because it inhibits the ovulation process. The microbiological transformation of 192 using Cunninghamella elegans produced four hydroxylated compounds (Figure 26) [94].…”
Section: Microbiological Transformations Of Steroidsmentioning
confidence: 99%
“…Biocatalysts can be used for regio-and stereo-selective reactions, or to introduce chirality in a way that would be very difficult, if not impossible, with classical chemical syntheses [4]. A number of studies have shown that several androgenic steroids have been biotransformed by fungi into metabolites with numerous biological properties [5] [6] [7]. Because of their stereochemistry (presence of many asymmetric centres and inert hydrocarbon skeletons), the hydroxylation, oxidation and epoxidation of steroids are difficult tasks for organic chemists.…”
Section: Introductionmentioning
confidence: 99%